PERFORMANCE OF ESG INDEX: AN EMPIRICAL COMPARISON OF S&P BSE 100 ESG INDEX WITH SELECTED BSE STOCK INDEXES - V, Dr. Amruthavarshini.; B, Harsha. (The journal of contemporary issues in business and government, 2022)
Environmental, Social and Governance (ESG) are the three central factors in measuring sustainability of an investment. Investors are increasingly applying these non-financial factors as a part of their analysis process to identify material risks and growth opportunities. Therefore, there is a need to study the performance of ESG stocks for better investment decisions. The objective of the paper is to empirically examine the performance of S&P BSE 100 ESG Index with other selected BSE stock indexes. For the study, Daily and monthly adjusted closing prices of respective index during the period from 1st Jan 2018 to 31st Dec 2021 have been collected from BSE and Yahoo finance.. Then index prices have been converted into simple percentage returns. The risk-free rate is calculated as the daily average implicit yield on 364 days treasury bills over the study period. Next Karl Pearson’s Co-efficient of correlation is used to study the relationship among these portfolios. For the performance evaluation, portfolio beta and risk adjusted measures like Sharpe ratio, Treynor ratio and Jensen measure have been used. T-test is used to check whether the mean returns of the portfolios are significantly different or not. The study reveals that Performance of the ESG stock portfolio has outperformed when compared to Blue chip and Large cap stock portfolio as the Sharpe, Treynor and Jensen ratios are highest compare to rest of the portfolios. It is found that daily returns of the ESG stock portfolio are consistent with the monthly returns. During this study period, ESG stocks have performed better and there is no significant difference among the portfolios in terms of daily returns.